Role of Social Media in Learning English Language - Pokhrel, Yog Raj (BARUN Journal, 2025)
This study aims to explore the role of social media in teaching English language to the undergraduate college students. It covers the social media like Facebook, Instagram, Twitter, or What’s App. The effectiveness of those social media platforms in learning English language was observed in this study. Quantitative approach is implied with a survey method which includes questionnaires. The Information and Communication Technology (ICT) tools, competency to use social media elements are some parts of learning English language. According to the result, social media play an important role, and they help them improve all their skills in the English language. The findings indicated that the students learn new things, skills and gather new knowledge using social media. Hence, the learners may be encouraged to engage themselves to use social media in English to improve their proficiency.